SISTEM SELEKSI PENERIMAAN TENAGA KERJA OUTSOURCING MENGGUNAKAN ALGORITMA C5.0 BERBASIS ANDROID (STUDI KASUS : PT. SINERGI INDO PRIMA MEDAN) - Aryati Aryati; Samsudin Samsudin; M Fakhriza (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2022)
PT. Sinergi Indo Prima is a company that supports employment services or called outsourcing. Services included in the outsourcing are security guards, administrative staff, factory workers, drivers, sales promoters, and cleaning services. As for looking for prospective workers PT. Sinergi Indo Prima Medan has a problem, namely the system is still manual, data input only uses Microsoft Excel or does not have a professional decision support system in selecting prospective workers who meet the criteria, so that the prospective workers to be distributed are not in accordance with the competencies of the areas of expertise assigned to them. required by companies in need. In this study the author uses the Rapid Application Development (RAD) development method, using the C5.0 Algorithm, with the support of Unified Modeling Language (UML) tools using the Java programming language based on Android Studio, Microsoft Visio and Umlet to design the interface. The results of the design of the recruitment selection system for outsourcing prospective workers is an application called AKSIP which is used for the data selection process for prospective workers in each job category, while the results of testing data from 6 job categories using the C5.0 Algorithm achieve a success percentage of accuracy value of 94%